2014
DOI: 10.1177/0300060514527913
|View full text |Cite
|
Sign up to set email alerts
|

Duloxetine in the treatment of burning mouth syndrome refractory to conventional treatment: A case report

Abstract: Patients with burning mouth syndrome (BMS) report burning sensation and pain involving the tongue and oral mucosa without any apparent medical or dental cause. The pathogenesis of this syndrome remains unclear and there is currently no standard treatment. BMS is, therefore, often misdiagnosed and its management is complex. This lack of clinical expertise may result in decreased health-related quality of life and increased psychological distress among patients with BMS. The present case report involves a 77-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In fact, two single case reports and one observational study with small number of subjects have reported the effects of SNRIs on BMS patients [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, two single case reports and one observational study with small number of subjects have reported the effects of SNRIs on BMS patients [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Duloxetine tends to have better analgesic effects at higher doses, and the recommended dose of duloxetine is generally 60 mg once daily [15]. In two single case reports, 60 mg/day of duloxetine was effective in refractory BMS patients [20,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of many pharmacological agents, including pregabalin, 18) topiramate, 19) duloxetine, 20) pramipexol, 21) and olanzapine, 22,23) has been reported in isolated cases or case series. In the present study, we reported the effectiveness of new pharmacologic agents that had not been discussed previously in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment modalities for BMS patients according to the literature are summarized in Table 1. 75,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107] Furthermore, Kuten-Shorrer et al evaluated the placebo effect in 12 published RCTs regarding the treatment of BMS. Despite limitations of the studies (study design, sample size, duration of therapy, placebo control), they found a positive placebo response in 6 out of 12 studies.…”
Section: Managementmentioning
confidence: 99%